Pregnancy‐associated breast cancer in a contemporary cohort of newly diagnosed women. Issue 4 (25th August 2019) - Gooch, Jessica C.; Chun, Jennifer; Kaplowitz, Elianna; Guth, Amber; Axelrod, Deborah; Shapiro, Richard; Roses, Daniel; Schnabel, Freya
Abstract: Pregnancy‐associated breast cancer (PABC) refers to breast cancer (BC) diagnosed during pregnancy, lactation, or in the postpartum period. There is evidence that PABC is associated with a poorer prognosis, and that the development of the disease is influenced by the unique hormonal milieu of pregnancy. The purpose of this study was to investigate the clinicopathologic characteristics associated with PABC in a contemporary cohort of women with newly diagnosed BC. Our institutional Breast Cancer Database was queried for women diagnosed with BC between 2009‐2018 who had at least one full‐term pregnancy (FTP). Variables of interest included patient demographics and clinical and tumor characteristics. PABC was defined as breast cancer diagnosed within 24 months of delivery. Statistical analyses included Pearson's chi‐square and logistic regression. Out of a total of 2202 women, 46 (2.1%) had PABC. Median follow‐up in the total cohort was 5.5 years. After adjusting for age at first FTP, PABC was associated with younger age at diagnosis, older age at first FTP, non‐Caucasian race, BRCA positivity, presentation with a palpable mass, higher pathologic stage, higher histologic grade, and ER‐negative and triple‐negative receptor status. The association of PABC with non‐Caucasian race may be reflected in the increased proportion of triple‐negative breast cancers in the PABC group. PABC was also associated with older age at first FTP. As more women delay childbearing, risk for PABC may increase. Our findings suggest that women who become pregnant at older ages should be followed carefully during pregnancy and the postpartum period, especially if they are BRCA mutation carriers. The optimal approach for monitoring older women during pregnancy and the postpartum period is unclear.